Colombia : Third Review Under the Stand-By Arrangement and Request for a Waiver of Nonobservance of Performance Criterion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper discusses Colombia Third Review Under the Stand-By Arrangement (SBA) and Request for Waiver of Nonobservance of Performance Criterion. Under the authorities' program, economic performance has improved considerably. Real GDP rose by 3.7 percent in 2003 and 3.8 percent in the first quarter of 2004, while inflation fell to 5.4 percent year over year in May, lower than expected. Solid export growth, together with improved confidence, has strengthened the external position. Fiscal policy is on track, and almost all structural reforms continue to advance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet